The Application of Acceptance Models to Human Resource Information Systems: A Literature Review - Menant, Lou; Gilibert, Daniel; Sauvezon, Céline (Frontiers in Psychology, 2021)
The acceptability of technologies has been the subject of many studies in recent years which have led to the emergence of general models, which do not take account of contextual specificities such as the activities proposed by these technologies. Human Resource Information Systems (HRIS), which are becoming extremely prevalent in organisations and whose acceptability has been the subject of several studies and different modellings, have not to our knowledge inspired the creation of an integrative acceptability model. We would like to present a literature review based on the analysis of 23 articles which deal with the classic variables of perceived usefulness and ease of use of these IT solutions for employees and HR Managers. The presentation of this analysis is structured around the general TAM and UTAUT models and aims to identify the variables to these models added in the literature, with regard to the intention to use HRIS. The discussion and perspectives for future research propose (a) a synthesis of predictors specific to HRIS, (b) to address the acceptability of HRIS from the point of view of Organisation-HRIS-User interrelations (c) reasons which might induce employees to adopt HRIS solutions.